Structure‐Based Design of Drugs and Other Bioactive Molecules. Edited by Arun K. Ghosh and Sandra Gemma. Issue 5 (17th March 2015) - Stocks, Michael
<x xml:space="preserve">Abstract</x> Wiley‐VCH, Weinheim 2014. 474 pp., hardcover, €99.00.—ISBN 978‐3‐527‐33365‐3